2012
DOI: 10.1128/jb.01193-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Enterobacter radicincitans DSM16656 T , a Plant Growth-Promoting Endophyte

Abstract: b Enterobacter radicincitans sp. nov. DSM16656T represents a new species of the genus Enterobacter which is a biological nitrogen-fixing endophytic bacterium with growth-promoting effects on a variety of crop and model plant species. The presence of genes for nitrogen fixation, phosphorous mobilization, and phytohormone production reflects this microbe's potential plant growth-promoting activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 8 publications
1
34
0
Order By: Relevance
“…Parts of this segment have been previously found in the IncHI2 plasmid pIMP4-SEM1 (encoding IMP-4 M␤L) from Salmonella enterica Typhimurium, isolated from a companion animal (19), and plasmid pKrDSM16656L from Kosakonia radicincitans, isolated from a plant (20), suggesting that this segment is involved in the survival of the microbe under environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Parts of this segment have been previously found in the IncHI2 plasmid pIMP4-SEM1 (encoding IMP-4 M␤L) from Salmonella enterica Typhimurium, isolated from a companion animal (19), and plasmid pKrDSM16656L from Kosakonia radicincitans, isolated from a plant (20), suggesting that this segment is involved in the survival of the microbe under environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Production of auxins, especially indole-3-acetic acid (IAA), is frequently found in growth-promoting endophytes (Witzel et al 2012). Auxins play a cardinal role in elevation of root growth and development, and act antagonistically to ethylene.…”
Section: Plant Hormone Statusmentioning
confidence: 99%
“…Nonetheless, transfer of phosphate to the plant was neither assessed nor can it be inferred from the nutrient content in shoots, and therefore, this mechanism should be verified in future experiments. Kosakonia species, previously classified into the genus Enterobacter (Brady et al 2013), have been reported as PGPR in rice (Peng et al 2009), groundnut (Madhaiyan et al 2010), and winter wheat (Witzel et al 2012). Previous studies showed that the production of phytohormones and N 2 fixation were the main plant growth-promoting mechanisms in winter wheat (Scholz-Seidel and Ruppel 1992), while in Arabidopsis thaliana, K. radicincitans not only enhanced plant growth but also induced priming of the immune response (Brock et al 2013).…”
Section: Discussionmentioning
confidence: 98%